France's disruptive Zeitenwende: As a consequence of Russia's war against Ukraine, Paris and Berlin adapt their security and defence policy - and bilateral divergences are increasing - Sven Arnold; Claudia Major (Stiftung Wissenschaft und Politik (SWP), 2024)
Russia's fullscale invasion of Ukraine since 24 February 2022 has not shaken France's security policy as fundamentally as it has Germany's. France sees its previous goals confirmed, particularly in terms of strengthening Europe's strategic sovereignty. Nevertheless, it has been adapting in many areas in order to continue pursuing its ambitions under changed external conditions. This led to a continuity in security policy objectives - with notable adjustments in the means and direction. These include France's now active support for the enlargement of the European Union (EU) and the North Atlantic Treaty Organization (NATO) as well as its increased commitment within NATO. This has also partly dispelled the irritation among European partners that President Emmanuel Macron caused in 2022 with his statements about the need to reach out to Russia. However, substantial differences between Germany and France remain and have intensified in some cases, making bilateral cooperation more complicated.
Keywords: 320; Zeitenwende; French security policy; Revue Stratégique; Verteidigungspolitische Richtlinien; VPR; European Defence Agency; Europe's Defence Technological and Industrial Base; EDTIB; Versailles Agenda; EU enlargement; Ukraine; European Political Community; EPG; European Union Military Assistance Mission; EUMAM; enhanced Forward Presence; eFP; Very High Readiness Joint Task Force; VJTF